2006
DOI: 10.1002/neu.20230
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin‐2 differentially regulates the anterograde axonal transports of acetylcholinesterase and choline acetyltransferase in Drosophila

Abstract: Choline acetyltransferase (ChAT) and acetylcholinesterase (AChE) are involved in acetylcholine synthesis and degradation at pre- and postsynaptic compartments, respectively. Here we show that their anterograde transport in Drosophila larval ganglion is microtubule-dependent and occurs in two different time profiles. AChE transport is constitutive while that of ChAT occurs in a brief pulse during third instar larva stage. Mutations in the kinesin-2 motor subunit Klp64D and separate siRNA-mediated knock-outs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 52 publications
5
26
0
Order By: Relevance
“…These observations suggested that, unlike the kinesin‐1 mutants , the axon channels were not blocked in the Klp64D mutant. Together with the previous data , these results established that ChAT transport by kinesin‐2 in the axons requires an interaction with the KLP64D tail.…”
Section: Resultssupporting
confidence: 84%
“…These observations suggested that, unlike the kinesin‐1 mutants , the axon channels were not blocked in the Klp64D mutant. Together with the previous data , these results established that ChAT transport by kinesin‐2 in the axons requires an interaction with the KLP64D tail.…”
Section: Resultssupporting
confidence: 84%
“…Phosphorylated cJun N-terminal Kinase (p-JNK) localization was found throughout the neuron (Figure S4E), complementary to larval nerves (Figure S5ABC) [53]. An antibody against Choline Acetyltransferase (ChAT), a cholinergic neuron marker, was localized in high concentrations to the cell body and minimally in projections and growth cones (Figure S4F), similar to what was previously observed in whole mount larvae [54][56] (Figure S5ABC). Highwire, a negative regulator of NMJ growth [57][59], localized to neuronal cell bodies and growth cones, and minimal localization was seen within projections (Figure S4G).…”
Section: Resultssupporting
confidence: 78%
“…To test this possibility, we examined their localizations in tissues. Both an available anti-Klp64D antibody (Baqri et al, 2006) and our newly generated antibodies specifically detected Klp64D protein on a western blot, but could not recognize the protein in tissues by immunocytochemical staining. Thus, we generated a transgenic fly line that carries UAS-Klp64D-HA (Hemagglutinin).…”
Section: Klp64d Shows Overlapping Subcellular Localization With Arm Amentioning
confidence: 94%